Combination therapy for high-volume versus low-volume metastatic hormone-sensitive prostate cancer: A systematic review and network meta-analysis - Jian, Tengteng; Zhan, Yang; Yu, Ying; Yu, Kai; Hu, Rui; Wang, Jixue; Lu, Ji (Frontiers in Pharmacology, 2023)
Purpose: To conduct a systematic review and network meta-analysis (NMA) to compare the efficacy of currently available combination therapies in patients with metastatic hormone-sensitive prostate cancer (mHSPC). Methods: Qualified publications were searched in the PubMed, Embase, and Cochrane CENTRAL databases. Overall survival (OS) and radiographic progression-free survival (rPFS) were indirectly compared and assessed using NMA and the surface under the cumulative ranking curve, respectively. Adverse events (AEs) were also compared. Results: Eighteen publications from 12 trials were analyzed in the NMA. In the overall population, triplet therapy was ranked first for OS (hazard ratio [HR]: 0.57, 95% credible interval [CrI]: 0.48–0.67) and rPFS (HR: 0.33, 95% CrI:0.26–0.41) compared with androgen deprivation therapy (ADT) with or without standard non-steroidal antiandrogen. In high-volume mHSPC, triplet therapy was also ranked first in OS (HR, 0.57; 95% CrI:0.44–0.75) and rPFS(HR, 0.29; 95% CrI: 0.23–0.37). Specifically, abiraterone triplet therapy was ranked first in OS (HR, 0.52; 95% CrI:0.38–0.72) and rPFS (HR, 0.28; 95% CrI:0.21–0.38) among all therapies. ADT plus rezvilutamide was ranked first among doublet therapies (OS: HR, 0.58; 95% CrI:0.44–0.77; rPFS: HR, 0.44; 95% CrI:0.33–0.58). In low-volume mHSPC, doublet and triplet therapies were ranked first in OS (HR:0.68, 95% CrI:0.58–0.80) and rPFS (HR:0.37, 95% CrI:0.25–0.55), respectively. ADT plus apalutamide was ranked first in OS among all therapies (HR:0.53, 95% CrI:0.35–0.79), whereas enzalutamide triplet therapy was ranked first in rPFS (HR:0.27, 95% CrI:0.15–0.51). ADT plus rezvilutamide showed a relatively lower incidence of AE among all therapies (OR:1.00, 95% CrI:0.31–3.15), and a lower risk of specific AEs among doublet therapies, particularly regarding seizure (OR, 0.29; 95% CrI:0.01–8.18) and fatigue (OR, 0.96; 95% CrI:0.63–1.46). Docetaxel-based doublet or triplet therapies significantly increased the risk of any AEs or grade ≥3 AEs. Conclusion: Triplet therapy was the best treatment option for the overall population. In high-volume mHSPC, triplet therapy and ADT plus rezvilutamide had the greatest potential to benefit patients. Patients with low-volume mHSPC were most likely to benefit from ADT plus androgen receptor-targeted agents. Triplet therapy was associated with a higher risk of AEs than the other therapies. Systematic Review Registration:https://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42022375347, identifier PROSPERO:CRD42022375347.